Fonem Bahasa Arab Dan Bahasa Gayo: Analisis Kontrastif Dan Dampaknya Pada Penutur Gayo - Salam, Mahdi Wahyuni; Zulfikar, Dede (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Gayo language, as part of the local cultural heritage, exhibits unique features in its phoneme system, consisting of consonant and vowel arrangements that can influence the sounds of a second language with differing phonemes. The aim of this study is to identify and describe the phonological errors made by the students of Dayah Terpadu Az Zahra in pronouncing Arabic, particularly from the perspective of articulation points and letter characteristics. The research method used is Contrastive Linguistic Analysis, which seeks to identify and establish phonological differences between Gayo (B1) and Arabic (B2). The analysis is conducted by contrasting the articulation points and characteristics of the letters of both languages, followed by classifying the phonological errors. The findings reveal that the students of Dayah Terpadu Az Zahra in Takengon, Central Aceh, made errors in pronouncing 12 Arabic phonemes, with articulation mistakes caused by differences in articulation points and letter characteristics between the two languages. These findings indicate significant phonological barriers affecting the mastery of Arabic phonemes by native Gayo speakers.